Perspektif Informasi Keruangan (Geospasial) dalam Melihat Fenomena Demam Berdarah Dengue - Andri Rualiansyah (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Dengue hemorrhagic fever (DHF) is important public health problem in Indonesia and often cause Unusual with high mortality. this is possible regarding the condition of spatial planning is still not well ordered, the total population continues to swell, the weather isconducive to the development of mosquitoes, and the added concern that the low population and government to a healthy environment. Factors that related with DHF spreading, can be analyzed from the perspective of spatial information (geospatial). Hence the necessary cooperation geometrics specialists, regionalplanners, and health professionals in preventing the spread of dengue viruses. The presence of remote sensing technology and Geographic Information Systems (GIS) is very useful as aprovider of continuous data and as a tool that can visualize and manage the spatial and textual data of the factors that influence the spread of dengue. There are many products from remote sensing image interpretation that can be relied upon in the monitoring of dengue phenomenon, frequently used images such as Ikonos, Quickbird, Aster, ALOS, Landsat and many more types of images that can be used in the interpretation of phenomena in the monitoring of DHF. With the results of remote sensing geospatial information, the control and prevention of the spread of dengue can be carried out effectively and efficiently. Thus, all activities can be done by planning a very mature, so that control programs can be done with the right